Basque childrens camp : inter-departmental correspondence - Harries, E. P.
039-0110-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From E.P. HARRIES. Department. ORGANISATION. To SIR WALTER CITRINE. Date 28th May, 1937. SUBJECT: BASQUE CHILDRENS CAMP. I had a long telephone talk with D.R. Grenfell this morning regarding the above Camp. He says that it was discussed at length at the meeting of the Joint Committee for Spanish Relief on Wednesday, and he agrees with a rumour which I had heard that Isable [Isabel] Brown and her husband took a prominent part in the discussion was correct, although he did not know the person was her husband. He (Grenfell) was in the Chair. I told him we were contemplating complete severance from the whole idea and that we did not feel that the money which the public and the Movement were collecting as a result of our appeal, should be wasted and mis-used in the way it was being done. I asked him why a meeting of the Basque Children's Camp Committee had not been called at which our people could be present. He could not explain. I told him very bluntly (the conversation took place in Mr. Middleton's room with Miss Sutherland present) that he was being used as a camouflage to keep us quiet while the liberals and tories mismanaged the whole affair. With Mr. Middleton's and Miss Sutherland's concurrence I asked for a meeting of the Basque Children's Camp Committee either here or in Southampton on Tuesday or Wednesday of next week. He said that he had told Macnamara and Wilfred Roberts who were both at the Camp to-day, that they must re-place the present Camp Manager, Brunton [Brinton]. He is going to 'phone the Camp later to find out if this has happened. The 2,000 children mentioned in my report as being in the Girl Guides Camp should be 200. Grenfell has again phoned. He has spoken to Wilfred Roberts' secry at the camp & she says things are better. 1000 children will have left by Monday. EPH 292/946/39/110